Dinamika Kelompok Tani di Desa Gendayakan Kecamatan Paranggupito Kabupaten Wonogiri - Aulia Rahma Faizati; Emi Widiyanti; Putri Permatasari (Universitas Sebelas Maret, 2023)
Group dynamics is a process and interaction that aims to improve the achievement of the group’s goals. This study aimed to assess the level of farmer group dynamics in Gendayakan Village, Paranggupito Sub-district, Wonogiri Regency. The basic research method used in this research is quantitative with survey techniques. The research location was selected purposively in Gendayakan Village, Panggupito Sub-district, Wonogiri Regency. Sampling using a proportional random sampling technique by taking 63 farmer group members as respondents. Descriptive analysis to provide an overview of the level of farmer group dynamics was carried out using an ordinal scale as a reference for measuring the level of group dynamics. The results of this study indicated that the level of farmer group dynamics in Gendayakan Village is classified in the moderately dynamic category, indicating that the elements of farmer group dynamics in Gendayakan Village are quite well run. However, it is expected to maintain group dynamics and interaction between fellow members and carry out group activities to achieve group goals.